Cyto- and bio-compatibility assessment of plasma-treated polyvinylidene fluoride scaffolds for cardiac tissue engineering - Kitsara, Maria; Revet, Gaëlle; Vartanian-Grimaldi, Jean-Sébastien; Simon, Alexandre; Minguy, Mathilde; Miche, Antoine; Humblot, Vincent; Dufour, Thierry; Agbulut, Onnik (Frontiers in Bioengineering and Biotechnology, 2022)
As part of applications dealing with cardiovascular tissue engineering, drop-cast polyvinylidene fluoride (PVDF) scaffolds have been treated by cold plasma to enhance their adherence to cardiac cells. The scaffolds were treated in a dielectric barrier device where cold plasma was generated in a gaseous environment combining a carrier gas (helium or argon) with/without a reactive gas (molecular nitrogen). We show that an Ar-N2 plasma treatment of 10 min results in significant hydrophilization of the scaffolds, with contact angles as low as 52.4° instead of 132.2° for native PVDF scaffolds. Correlation between optical emission spectroscopy and X-ray photoelectron spectroscopy shows that OH radicals from the plasma phase can functionalize the surface scaffolds, resulting in improved wettability. For all plasma-treated PVDF scaffolds, the adhesion and maturation of primary cardiomyocytes is increased, showing a well-organized sarcomeric structure (α-actinin immunostaining). The efficacy of plasma treatment was also supported by real-time PCR analysis to demonstrate an increased expression of the genes related to adhesion and cardiomyocyte function. Finally, the biocompatibility of the PVDF scaffolds was studied in a cardiac environment, after implantation of acellular scaffolds on the surface of the heart of healthy mice. Seven and twenty-eight days after implantation, no exuberant fibrosis and no multinucleated giant cells were visible in the grafted area, hence demonstrating the absence of foreign body reaction and the biocompatibility of these scaffolds.